Epstein Barr Virus Interleukin 10 Suppresses Anti-inflammatory Phenotype in Human Monocytes - Jog, Neelakshi R.; Chakravarty, Eliza F.; Guthridge, Joel M.; James, Judith A. (Frontiers in Immunology, 2018)
Epstein Barr virus (EBV) is a gamma herpes virus associated with certain malignancies and autoimmune diseases. EBV maintains latency in B cells with occasional reactivation, in part by overcoming the host immune response with viral homologs of several human proteins. EBV interleukin 10 (vIL-10), a lytic phase protein, is a homolog of human IL-10 (hIL-10). The effect of vIL-10 on human monocytes, which are one of the first immune cells to respond to infection, is not known. To understand the role of vIL-10, monocytes from peripheral blood mononuclear cells were stimulated with hIL-10 or vIL-10. Human IL-10 stimulated STAT3 phosphorylation, which is required for suppression of inflammatory responses. However, vIL-10 induced significantly lower phosphorylation of STAT3 compared to hIL-10, and was less efficient in downregulating inflammatory genes. vIL-10 significantly reduced the expression of scavenger receptor CD163 on monocytes, suggesting inhibition of M2 polarization. Furthermore, uptake of apoptotic cells was reduced in vIL-10-stimulated monocytes compared to hIL-10-stimulated monocytes. A neutralizing antibody to IL-10R1 inhibited STAT3 phosphorylation induced by either hIL-10 or vIL-10, suggesting that vIL-10 signals through IL-10R1. Interestingly, vIL-10 suppressed hIL-10-induced STAT3 phosphorylation and inhibited upregulation of suppressors of inflammatory response by hIL-10. We further show that vIL-10 levels were significantly higher in plasma samples from systemic lupus erythematosus (SLE) patients compared to matched unaffected controls. vIL-10 levels did not correlate with hIL-10 levels, but were associated with levels of IgA antibodies to EBV viral capsid antigen, which is an indirect measure of viral reactivation. We propose that the suppression of hIL-10- induced anti-inflammatory genes by vIL-10, together with an increase in inflammatory gene expression, may overcome the anti-inflammatory effects of hIL-10 and exacerbate autoimmune responses in systemic autoimmune diseases.